2017
DOI: 10.3174/ajnr.a5336
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Features of the Cerebellum in Adult-Onset Neuronal Intranuclear Inclusion Disease: 8 Cases

Abstract: Neuronal intranuclear inclusion disease is a neurodegenerative disorder pathologically characterized by eosinophilic hyaline intranuclear inclusions. A high-intensity signal along the corticomedullary junction on DWI has been described as a specific MR imaging finding of the cerebrum in neuronal intranuclear inclusion disease. However, MR imaging findings of the cerebellum in neuronal intranuclear inclusion disease have not been fully evaluated. Here, we review MR imaging findings of the cerebellum in a series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 23 publications
4
41
0
Order By: Relevance
“…MRI results in two of five patients revealed high-intensity signals in the middle cerebellar peduncles and in the paravermal area on FLAIR images and in the corticomedullary junction on DWI, similar to those in patients with NIID ( Fig. 1e-h) [6,12,16].…”
Section: Discussionsupporting
confidence: 67%
“…MRI results in two of five patients revealed high-intensity signals in the middle cerebellar peduncles and in the paravermal area on FLAIR images and in the corticomedullary junction on DWI, similar to those in patients with NIID ( Fig. 1e-h) [6,12,16].…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, it should be considered that NIID patients may not produce apparent DWI abnormalities, depending on the timing of imaging. It was reported that cerebellar abnormalities, including high-signal intensity on FLAIR in the cerebellar hemisphere besides the vermis, are specific findings in NIID [ 10 ]. This cerebellar abnormality was confirmed in our case even when there were no DWI abnormalities, which indicates that abnormal cerebellar findings on FLAIR may be effective for diagnosing NIID, regardless of the absence of DWI abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have indicated that the continuous linear DWI high-intensity signal which rarely extended into the deep white matter is a characteristic feature for diagnosis. [7] Abnormal hyperintense signal firstly appeared in the frontal lobe, then spread to the parietal and occipital lobe. The signal distributed symmetrically along the corticomedullary junction, related with spongiotic changes in white matter proximal to the U-fibers.…”
Section: Discussionmentioning
confidence: 99%